Public health: the development of a discipline. Volume 1. From the age of Hippocrates to the progressive era (New Brunswick, N.J., 2008)
"Public health as a discipline grew out of traditional Western medicine but expanded to include interests in social policy, hygiene, epidemiology, infectious disease, sanitation, and health education. This book, the first of a two-volume set, is a collection of important and representative historical texts that serve to trace and to illuminate the development of conceptions, policies, and treatments in public health from the dawn of Western civilization through the Progressive Era of the early twentieth century. "